UMPSA shines at MTE 2024, won a special award, 2 gold, 5 silver and 1 bronze - Safriza, Baharuddin (UMPSA, 2024)
KUALA LUMPUR, 24 February 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continued to shine when its researchers won a Special Award, two gold, five silver and one bronze medals at the Malaysia Technology Expo (MTE) 2024.